2017
DOI: 10.4209/aaqr.2016.05.0198
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Indoor and Outdoor Particulate Matter (PM2.5, PM10) in Doha, Qatar

Abstract: ABSTRACTΤhe extreme weather conditions in Middle East Area led to the construction of tightly sealed, air conditioned buildings, characterized by indoor air quality deterioration. This study presents the results of chemical characterization of outdoor and indoor PM 2.5 and PM 10 in Doha city, over a two-month period including normal days and dust events, aiming at identifying the factors affecting the indoor air of an office building. The WHO guideline values were exceeded in 100% of the outdoor measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 51 publications
3
42
1
2
Order By: Relevance
“…with EF of 490 and 430 for both elements, respectively. On the other hand, the significant enrichment of Ca is in agreement with the domination of carbonate matter as reported earlier for studies in Qatar and other Arabian Peninsula countries[15][17][18][49].…”
supporting
confidence: 89%
“…with EF of 490 and 430 for both elements, respectively. On the other hand, the significant enrichment of Ca is in agreement with the domination of carbonate matter as reported earlier for studies in Qatar and other Arabian Peninsula countries[15][17][18][49].…”
supporting
confidence: 89%
“…Previous indoor air quality studies in Kuwait have investigated school classrooms and homes [20][21][22][23][24]. Other studies in the region examined indoor and outdoor PM concentrations during dust storm events [25,26]. The harsh climate conditions in the Gulf led to the construction of tightly sealed, air-conditioned buildings [26].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in the region examined indoor and outdoor PM concentrations during dust storm events [25,26]. The harsh climate conditions in the Gulf led to the construction of tightly sealed, air-conditioned buildings [26]. However, very little is known about the impact of dust storms on indoor levels of fine (PM 2.5 ) and coarse particles (PM 2.5-10 ) in Kuwait.…”
Section: Introductionmentioning
confidence: 99%
“…The most dominated elemental species were Zn, Ba, and Pb, including high levels of xylene and limonene (Eman et al, 2016). The presence of these elemental-PM based aerosols suggested infiltration and penetration of PMs via ventilation systems, windows, and building cracks, which were the main causes of indoor air pollution in the buildings in Doha (Saraga et al, 2017).…”
Section: Air Pollutants In Qatarmentioning
confidence: 99%
“…For all of these countries, most indoor air pollution studies have been focused on measuring the concentration levels and characterization of chemical species. Previous reviews have shown that particulate matters (PMs), carbon monoxide (CO), carbon dioxide (CO 2 ), sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ) and heavy metals were the major indoor air pollutants in the GCC countries (Abdul-Wahab and Al-Rehaili, 1999;Al Mulla et al, 2015;Argyropoulos et al, 2016;Elsayed et al, 2016;Farahat, 2016;Omidvarborna et al, 2018;Saraga et al, 2017). Recent studies in KSA have identified Radon ( 222 Rn) gas as another indoor air pollutant (Abo-Elmagd et al, 2018;Alghamdi and Aleissa, 2014).…”
Section: Introductionmentioning
confidence: 99%